Tax reform on the brink of fiscal dominance: a political economy model - Rogério L. F. Werneck (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2005)
With an overindebted public-sector, Brazil has been on the brink of a fiscal dominance problem for quite a long time. The term has been usually associated to a situation in which monetary policy becomes subordinated to fiscal needs. This paper calls attention to broader implications of prolonged exposure to impending fiscal dominance. A highdebt environment may make perfectly reasonable fiscal-reform initiatives seem extremely risky. Without any room to absorb revenue losses, in a complex fiscalfederalism arrangement, the government is bound to recurrently see badly needed tax reform, which could lead to a much less distorting tax system, as an unaffordable adventure. The paper is structured in the following way. The next section presents stylized facts that have been underlying a whole decade of unsuccessful tax-reform attempts in Brazil. Section 3 shows how the combination of those facts creates very unfavorable conditions for the approval of the kind of tax reform the country needs. A simple political economy model is developed in section 4. Simulations based on the model are analyzed in sections 5 and 6. Concluding remarks are presented in the last section.
Keywords: H20; H6; E62; H77; 330; tax reform; public debt; fiscal dominance; political economy; federalism; Brazil; Steuerreform; Theorie; Brasilien